Radioprotective effects of vitamin A against gamma radiation in mouse bone marrow cells - Vahid Changizi; Seyed Abolghasem Haeri; Sakineh Abbasi; Zahra Rajabi; Mohammad Mirdoraghi (MethodsX, 2019)
Radioprotectors by neutralizing the effects of free radicals, reduce the destructive effects of radiation. In this protocol article, the radioprotectory effect of vitamin A on micronuclei induced by gamma radiation was evaluated using micronucleus test. Vitamin A was injected intraperitoneally at 100 and 400 mg/kg two hours before 2 Gray (Gy) of gamma radiation. Animals were sacrificed after 24 h, and then specimens of the bone marrow were smeared and stained. The number of micronuclei were counted in polychromatic cells. Both dosage of vitamin A reduced the micronucleus in bone marrow polychromatic erythrocytes (MnPCE) level, which is statistically significant. The appropriate amount of vitamin A for protection in mice is 100 mg/kg, which protect the bone marrow of mice against clastogenic effects of radiation. The results of the study showed that vitamin A, possibly with an antioxidant mechanism, eliminates the effects of free radicals from ionizing radiation on bone marrow cells and reduces genetic damage. • The data of radioprotective effects of vitamin A showed that administration of 100 mg/kg vitamin A to mice prior to 2 Gy of gamma radiation has reduced the micronucleus levels in PCE cells by a factor of 2.62. • Administration of 100 mg/kg vitamin A, which is much smaller than LD50 of vitamin A (LD50 for intraperitoneal injection = 1510 ± 240 mg/kg) can protect mice. • Vitamin A reduces the harmful effects of ionizing radiation on DNA, due to the antioxidant activity and the trapping of free radicals produced by radiation, and diminish the genetic damage caused by radiation. • Vitamin A has no effect on the proliferation and differentiation rate of bone marrow cells. Protocol name: Vitamin A was injected intraperitoneally at 100 and 400 mg/kg two hours before 2 Gy of gamma radiation. Animals were sacrificed after 24 h, and then specimens of the bone marrow were smeared and stained. The number of micronuclei were counted in polychromatic cells [1–6], Keywords: Radioprotectors, Vitamin A, Micronucleus test, Gamma radiation